2020
DOI: 10.1108/ijcst-06-2019-0077
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the water evaporation rate of wet textile materials in a pre-defined environment

Abstract: Purpose The water evaporation rate (WER) is not only crucial for fabric drying, but also an important parameter affecting cooling from a body wearing sweat wetted clothing. The purpose of this paper is to predict the WERs of wet textile materials in a pre-defined environment. Design/methodology/approach The maximum water evaporation rate (WERmax) from a saturated surface in a pre-defined environment was first predicted based on the Lewis relationship between the evaporative and the convective heat transfer i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…For example, for the experiments for which this characteristics distance ( ) is 8 mm, the tangential air flux velocity at about 1 cm above the sample is of the In practice, textile drying occurs under a variety of conditions. In laboratory, the evaporation properties may be studied under some ambient humidity without controlling precisely the air flux [5], or with a tangential motion of the fabric with respect to ambient air [1,15]. In some cases the motion of a person wearing clothes is considered [12].…”
Section: B Drying Set Upmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, for the experiments for which this characteristics distance ( ) is 8 mm, the tangential air flux velocity at about 1 cm above the sample is of the In practice, textile drying occurs under a variety of conditions. In laboratory, the evaporation properties may be studied under some ambient humidity without controlling precisely the air flux [5], or with a tangential motion of the fabric with respect to ambient air [1,15]. In some cases the motion of a person wearing clothes is considered [12].…”
Section: B Drying Set Upmentioning
confidence: 99%
“…The current description of these processes relies on empirical models [11][12], global laws [1,[13][14][15][16] or statistical approaches [17], of limited applicability, for describing vapor or heat transfers through fabrics. For example, the mass flux of water evaporating from a surface covered by a textile is often considered to be simply proportional to the vapor pressure difference and to a material coefficient, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 The evaporation from the textile fabric was mainly considered when studying drying or cooling. [22][23][24][25] It was found that the relative air humidity is a main factor of the weather conditions that have principal influence on the evaporation intensity. 26 A thorough model to simulate capillary flow through fabrics while taking evaporation into account is still lacking, according to a comprehensive review of the literature in this area.…”
mentioning
confidence: 99%
“…20,21 The evaporation from the textile fabric was mainly considered when studying drying or cooling. 2225 It was found that the relative air humidity is a main factor of the weather conditions that have principal influence on the evaporation intensity. 26…”
mentioning
confidence: 99%